Tax Management and Deferred Tax Liabilities: Their Impact on Earnings Management - Tutty Nuryati; Uswatun Khasanah (Greenation International Journal of Tourism and Management, 2026)
This study aims to examine whether tax management and deferred tax liabilities can influence earnings management in companies in the properties & real estate sector listed on the Indonesia Stock Exchange during the 2018–2022 period. The population for this study consists of companies in the properties & real estate sector listed on the Indonesia Stock Exchange during the 2018–2022 period. The technique used to determine the sample in this study was purposive sampling. This study yielded a sample of 90 data points from 18 companies in the property and real estate sector over a 5-year period. The methods used in this study included descriptive statistical analysis, selection of a panel data regression model, testing of classical assumptions, multiple linear regression analysis, and hypothesis testing. The data required for this study consisted of secondary data in the form of financial statements available on the companies’ websites. Data analysis was conducted using Eviews version 13. The results of this study indicate that (1) tax management has a negative effect on earnings management, and (2) deferred tax expenses have a positive effect on earnings management.